Predicting burnout based on metacognitive beliefs and ‎ alexithymia mediated by optimism in nurses - Fatemeh sadat Hosseini Adl; Anis Khoshlahjeh sedgh (طب کار)
Introduction: The commitment of nurses to their jobs and patients has made nursing one of the human service professions susceptible to burnout syndrome. Therefore, the present study aimed to predict burnout based on metacognitive beliefs and alexithymia with the mediation of optimism in nurses. Materials and Methods: The current research was based on applied purpose and descriptive-correlational research design, specifically, structural equation modeling. The statistical population in this research was all the nurses in the hospitals of Qom City in 1401, and 200 nurses were randomly selected to participate in the present research. In this field study, the participants completed Burnout questionnaires by Meslech and Jackson (1986), a metacognition questionnaire by Wells and Cartwright-Houghton (2004), the Toronto dyslexia scale, and the Scheer and Carver optimism scale (1994). Data were analyzed using the Pearson correlation test and structural equation model using SPSS-24 and AMOS-24 software. Results: The results showed that the correlation coefficients between the variables are significant (p<0.01) and there is a positive and significant relationship between metacognitive beliefs and alexithymia with burnout in nurses, and there is a negative and significant relationship between optimism and burnout (p<0.01). Also, there was a negative and significant relationship between metacognitive beliefs and alexithymia and nurses' optimism (p<0.01). Also, the results of the path analysis showed that optimism plays a mediating role in the relationship between metacognitive beliefs and alexithymia with nurses' burnout. Conclusion: In general, current research emphasizes the importance of optimism in the relationship between metacognitive beliefs and alexithymia with nurses' burnout and optimism is an effective factor in reducing nurses' burnout.